Daily variations in the expression of miR-16 and miR-181a in human leukocytes - de Siqueira Figueredo, Diego; Gitaí, Daniel Leite Góes; de Andrade, Tiago Gomes (Blood cells, molecules, & diseases, 2015)
Circadian rhythms are controlled by a molecular mechanism that is organized in transcriptional and translational feedback loops of gene expression. Recent studies have been demonstrating the involvement of microRNAs (miRs) in post-transcriptional/translational control of circadian rhythms. In the present study we aimed to analyze the daily variations of miR-16 and miR-181a expression in human leukocytes. These miRs were independently associated with hematopoiesis and circadian rhythms in previous studies using experimental models. Peripheral blood from 6 subjects was sampled in a 24hour period for expression analysis using quantitative real-time PCR (RT-qPCR). Initially, we evaluated the expression stability of RNU6-2, RNU1A-1, RNU5A-1, SNORD-25, SCARNA-17 and SNORA-73A as candidate genes for normalization of RT-qPCR data. The combination of the four most stable genes (SNORA-73A/SCARNA-17/SNORD-25/RNU6-2) was indicated to provide a better normalization of miRs expressions. The results show a daily variation of miR-181a and miR-16 expression in human leukocytes, suggesting a potential participation of these genes in the modulation of the circadian rhythms present in blood cells.